2004
DOI: 10.1016/j.ejcnurse.2004.06.004
|View full text |Cite
|
Sign up to set email alerts
|

International Comparison of Factors Associated with Delay in Presentation for AMI Treatment

Abstract: Similar education about the need to seek treatment early in response to AMI symptoms may be applicable in Western and Eastern industrialised populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
96
1
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 21 publications
7
96
1
10
Order By: Relevance
“…Although the literature suggests that women may not feel vulnerable to AMI 18 and that cardiovascular diseases have been socially constructed as gender-specific, there was no interaction among gender, time of decision and judgment of the pain. Corroborating other studies [19][20][21][22][23][24] , the association of symptoms to heart problems resulted in faster decision making and arrival at a place of treatment, indicating that the recognition of the severity of symptoms appears to be crucial for immediate search of health care.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Although the literature suggests that women may not feel vulnerable to AMI 18 and that cardiovascular diseases have been socially constructed as gender-specific, there was no interaction among gender, time of decision and judgment of the pain. Corroborating other studies [19][20][21][22][23][24] , the association of symptoms to heart problems resulted in faster decision making and arrival at a place of treatment, indicating that the recognition of the severity of symptoms appears to be crucial for immediate search of health care.…”
Section: Discussionmentioning
confidence: 62%
“…Thus, the participants sought to endure the pain, relieve it, waited it to improve, concealed it and did not want to surrender to medical help immediately. Other studies have found that people who self-medicated 26 , waited for the pain to improve, maintained higher self control 23 and felt ashamed to ask for help 27 , taking longer to decide to seek a health service.…”
Section: Discussionmentioning
confidence: 98%
“…Patients kept a diary of all hospitalizations and were called monthly by a trained research assistant to obtain hospitalization data for 1 year following baseline data collection using a well‐validated life history method 26, 27. All hospitalizations were verified by medical record review.…”
Section: Methodsmentioning
confidence: 99%
“…Country specific challenges likely exist due to lack of resources, for example, salt restricted or healthy foods may be difficult to purchase in some countries [11] and weighing scales may not be affordable. There also are cultural differences in reactions to symptoms, as described in response to symptoms of a myocardial infarction [12]. In some countries it might be difficult or unusual to access a health care provider for HF symptoms.…”
Section: Introductionmentioning
confidence: 99%